Pertimbangan Perilaku Keputusan Pengadaan Alat Usaha UMKM Roti Jadul Sido Maju Marsudi - Naeni Amro; Munaa Nur ‘Aziizah; Endras Larasati (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to understand behavioral considerations in decision-making regarding business equipment procurement at UMKM Sido Maju Marsudi. This research applies a qualitative method with a case study approach. Primary data were collected through semi-structured interviews with the business owner. The findings reveal that equipment procurement decisions are not solely influenced by economic rationality but also by behavioral factors such as intuition, experience, and social values. The business owner balances financial benefits with non-financial satisfaction, including customer trust, product quality, and maintaining the traditional identity of “roti kering jadul.” The decision-making process is simple, experience-based, and guided by social recommendations, reflecting bounded rationality. Evaluations are carried out informally by observing production outcomes and customer feedback. This study concludes that behavioral and experiential aspects play a crucial role in shaping adaptive and sustainable business decisions among micro and small enterprises